(untitled) (Research, Society and Development, 2021)
The article aims to reflect on rural education from the perspective of rural teacher training and the teaching methodologies developed in the early grades of elementary school in multiseries classes. This study emerged from the master’s research project in teaching at the University of Vale do Taquari - Univates in the year 2020. The referred study had a bibliographic approach, having as theoretical reference authors of the field of study as: Hage; Parente; Arroyo, Caldart and Molina; Delboni and other authors that make us think about the highlighted issue. We also use some legal devices as a documentary source to highlight: LDB; documents (CNEC) and Decree No. 7,352, of November 4, 2010. This article highlights the need for specific training for teachers working in multi-grade classes in order to think about planning based on the possibilities of methodologies developed by teachers who process in multiseries classes in the initial grades of elementary education in rural education, in addition to the recognition of rural education as a modality that should be given due attention by education managers.